Clinical implications of current cardiovascular outcome trials with sodium glucose cotransporter-2 (SGLT2) inhibitors. (May 2018) - Lim, Soo; Eckel, Robert H.; Koh, Kwang Kon
Abstract: The final goal in the management of patients with type 2 diabetes (T2D) is reduction in cardiovascular (CV) complications and total mortality. Various factors including hyperglycemia contribute to these complications and mortality directly and indirectly. In recent years, large-scale CV outcome trials with new antidiabetic medications, such as dipeptidyl peptidase-4 (DPP4) inhibitors, glucagon-like peptide-1 (GLP1) receptor agonists, and sodium glucose cotransporter-2 (SGLT2) inhibitors, have been completed. Most clinical trials with DPP4 inhibitors have shown no inferiority compared with placebo treatments in terms of CV safety. However, they did not show benefits in terms of adverse CV events or mortality. CV outcome trials with GLP1 receptor agonists showed inconsistent results: lixisenatide did not show benefits in preventing major adverse CV events. In contrast, liraglutide and semaglutide (longer acting GLP1 receptor agonists) proved to be superior in terms of alleviating CV morbidity and mortality. Two large-scale CV outcome trials with SGLT2 inhibitors showed significant results: empagliflozin proved to be superior in preventing CV and all-cause mortality, and canagliflozin proved to be superior in preventing CV mortality but not all-cause mortality. So far, controlling cardiometabolic risk factors such as hemodynamic changes and weight loss by SGLT2 inhibitors are suggested to be the main mechanisms for these results. However, the risk–benefit profile for these new drugs will need further elucidation, and more studies are warranted to reveal the possible mechanisms. It will also be important to confirm these results from other ongoing trials with SGLT2 inhibitors. Highlights: Most clinical trials with DPP4 inhibitors have shown no inferiority compared with placebo treatments in terms of CV safety. CV outcome trials with GLP1 receptor agonists showed inconsistent results. Two large-scale CV outcome trials with SGLT2 inhibitors showed very significant results. Controlling cardiometabolic risk factors by SGLT2 inhibitors are suggested to be the main mechanisms.